Прогнозування вуглеводневих покладів на континентальному схилі Західно-Чорноморської западини (за атмогеохімічними та температурними даними) - Багрій, І.Д. (Геологічний журнал, 2010)
Обобщены результаты разработки и применения комплекса структурно-термоатмогеохимических методов для уточнения структурной модели объектов исследования, прогнозирования и оконтуривания участков, перспективных на поиски залежей нефти и газа. Приведены результаты комплексных исследований континентального склона Западно-Черноморской глубоководной впадины. По результатам выполненного комплекса определены дополнительные критерии прогнозного районирования перспективных площадей и оценки их перспектив на залежи углеводородов. The results of development and application of complex of integral thermo-atmogeochemical and structural surveying are generalized for clarification of structural model of objects of research, prognostication of areas, perspective on the searches of beds of oil and gas. The results of complex researches are resulted on perspective structures north-western, north-eastern shelves of the Black sea and continental slope of Western Black Sea Continental Slope. On results of the executed complex the additional criteria of the prognosis districting of perspective areas and estimation of their prospects on the bed of hydrocarbons are certain.